PROBLEM ANALOGATU GŁÓWNEGO W ANALOGII PROPORCJONALNOŚCI WŁAŚCIWEJ TRANSCENDENTALNEJ A DOWODZENIE ISTNIENIA BOGA - Czajczyk, Anna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The main thesis of this article can be expressed by way of the statement that this work is not a study of the structure of transcendental analogy of proper proportionality (the relationship of analogate – analogon), but that of a similar structure built upon the notion of “being” (the ratio of the essence – the existence). This is the basis for establishing the existence of the main analogate. The study draws attention to the plane of ontological realism, a notion on which M.A. Krąpiec authored the concept of transcendental analogy of proper proportionality. Therein, one can find the three descriptions of the primary analogate. The first tier of this is an analysis of how to implement the same transcendental relationship amongst all, above all, the relationship of being – being. The second tier is an analysis of radiated domestic perfection [ustopniowania]. The third tier is met by way of the analysis of existence as an act – this constituting “being”. In the first case, the emphasis is on the similarity overlap transcendental relationships, based on a common analogonie. The second is built upon the impossible analogates. These being sourced in the nonidentity analogate and analogon. The third is constructed upon the fact that the existence of the act cannot be explained by the elements inducing internal governance [wewnątrzbytowe]. Due to the last, in the first case, the analogate main reasoning appears to be sufficient to realize the same transcendental relationship in living entities. With regard to the second, maximal domestic perfection serves as the reason justifying the ontological diversity within the third as being of sufficient reason to update. These roads of investigation towards determining the primary analogate should not be considered separately, since in no case can one of the notions be ignored in ascertaining whether such is an analogate or an analogon. Yet such a study can be understood only in terms of serving as justification for the claim that “being” derives both from the “essence” (analogate) and from the “existence” (analogon), and also from the same path, that the transcendental is related to the determination of the primary analogate.